Da oferta da educação infantil em tempo integral à integralidade na educação: um estudo sobre o município de São Carlos/SP - Yabuki, Michele (2021)
We aim to present in this work the trajectory of Full-time Early Childhood Education and how this education modality has been configured historically and politically in the municipality of São Carlos, through bibliographic research revising authors whose works concern its development at national and municipal levels. We seek to analyze how the theme of Early Childhood Education has been presented in academic productions and for that we resort to the State of the Question as the first method. To outline the legal norms of Full-time Education that seek Integral Education and the concepts that surround these themes, we resort to bibliographic research as a second method and we come to the conclusion that the two concepts together are destined to offer a public quality policy that is based on children's rights to education. Finally, to search for the paths traced by the municipality of São Carlos in relation to the provision of Early Childhood Education, we used documentary research in the municipality's Education Department as a method. Research has shown that it is not enough just to offer full-time early childhood education, increasing the time the child stays in school, but to offer an integral and quality education, designed for that time. As a result, we found statistical data from the municipality that demonstrate a development in the quest to achieve the goals established in official municipal and national documents in relation to full-time Early Childhood Education, but as it was found during the studies, the municipality still needs to make the effort to provide a Full-Time Integral Education.